Selective Insolubility of α-Synuclein in Human Lewy Body Diseases Is Recapitulated in a Transgenic Mouse Model - Kahle, Philipp J. (American Society for Investigative Pathology, 2001)
α-Synuclein (α-SYN) is deposited in intraneuronal cytoplasmic inclusions (Lewy bodies, LBs) characteristic for Parkinson’s disease (PD) and LB dementias. α-SYN forms LB-like fibrils in vitro, in contrast to its homologue β-SYN. Here we have investigated the solubility of SYNs in human LB diseases and in transgenic mice expressing human wild-type and PD-associated mutant [A30P]α-SYN driven by the brain neuron-specific promoter, Thy1. Distinct α-SYN species were detected in the detergent-insoluble fractions from brains of patients with PD, dementia with LBs, and neurodegeneration with brain iron accumulation type 1 (formerly known as Hallervorden-Spatz disease). Using the same extraction method, detergent-insolubility of human α-SYN was observed in brains of transgenic mice. In contrast, neither endogenous mouse α-SYN nor β-SYN were detected in detergent-insoluble fractions from transgenic mouse brains. The nonamyloidogenic β-SYN was incapable of forming insoluble fibrils because amino acids 73 to 83 in the central region of α-SYN are absent in β-SYN. In conclusion, the specific accumulation of detergent-insoluble α-SYN in transgenic mice recapitulates a pivotal feature of human LB diseases.